On the inner disc structure of MWC480: evidence for asymmetries?. Issue 3 (28th September 2017) - Jamialahmadi, N.; Lopez, B.; Berio, Ph.; Matter, A.; Flament, S.; Fathivavsari, H.; Ratzka, T.; Sitko, M. L.; Spang, A.; Russell, R. W.
Abstract: Studying the physical conditions structuring the young circumstellar discs is required for understanding the onset of planet formation. Of particular interest is the protoplanetary disc surrounding the Herbig star MWC480. The structure and properties of the circumstellar disc of MWC480 are studied by infrared interferometry and interpreted from a modelling approach. New observations are driving this study, in particular, some recent Very Large Telescope Interferometer (VLTI)/MIDI data acquired in 2013 December. Our one-component disc model could not reproduce simultaneously all our data: the spectral energy distribution, the near-infrared Keck Interferometer data and the mid-infrared data obtained with the MIDI instrument. In order to explain all measurements, one possibility is to add an asymmetry in our one-component disc model with the assumption that the structure of the disc of MWC480 has not varied with time. Several scenarios are tested, and the one considering the presence of an azimuthal bright feature in the inner component of the disc model provides a better fit of the data.